Optimalisasi Manajemen Pembiayaan Pendidikan Berbasis Akuntabilitas dan Transparansi untuk Meningkatkan Mutu Pendidikan - Yessy Ardina Emilia; Dwi Cahyaningdyah (CV. ITTC INDONESIA, 2026)
Education financing management is an essential component in ensuring the sustainability and quality improvement of educational institutions. Effective, efficient, accountable, and transparent financial management contributes significantly to achieving educational goals and improving educational services. However, several challenges remain, including limited transparency, weak accountability systems, inefficient budget utilization, and unequal distribution of educational resources. This study aims to describe the concept of education financing management based on accountability and transparency, analyze its role in improving educational quality, and identify optimization strategies for effective financial management. This study employed a literature review approach by analyzing scientific journals, books, government regulations, educational policy documents, and research reports. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that accountability and transparency strengthen financial governance, increase public trust, enhance stakeholder participation, and support sustainable educational quality improvement. Optimization strategies include needs-based budgeting, digitalization of financial systems, strengthening human resource competencies, internal supervision, stakeholder involvement, and continuous monitoring and evaluation. Collaboration among government institutions, schools, communities, and all stakeholders is necessary to establish sustainable educational financial governance. Therefore, accountability and transparency should become the primary principles in educational financing management to achieve high-quality and equitable education.